PENGARUH MODEL PEMBELAJARAN OBSERVASI LAPANGAN TERHADAP HASIL BELAJAR IPS SD - Diyas Age Larasati (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
The aim of this research is for explaining the effects of field study model on social study results of elementary school students. This research is a quasi experimental with two subjects, that is experimental and control group. Learning results of both classes is measured by pretest and posttest, than that gain scores is calculated for further analysis. Data is analyzed by independent sample t test and processed by computer SPSS 16.0 for Windows program. The research results show that the field study model has a significant effect on social learning results. The average of gain score in experimental class is 17,81, while in control class is 12,42. Analysis process by independent sample t test show that data results show ñ value on 0,006 level. That value is more less than 0,05 (ñ<0,05). So the conclusion is ”the field study model has a significant effect on social study results of elementary school students”.